Vietnam’s STEM Education Landscape: Evolution, Challenges, and Policy Interventions (Journal of Contemporary Educational Policies and Practices, 2024)
In Vietnam, national policies increasingly prioritize STEM education, recognizing its critical role in developing future workforce skills. However, significant gaps remain between policy and practice. Currently, STEM education in Vietnam is primarily found in extracurricular activities, with limited systematic integration into the formal curriculum. Key challenges include inadequate teacher capacity, insufficient resources, sociocultural biases, and difficulties in translating national STEM goals into classroom practices. Future research should focus on several key areas to further strengthen STEM education in Vietnam. Evaluating effective curriculum models will help integrate STEM into the core curriculum more systematically. Assessing professional development programs will ensure that teacher training initiatives are effective and impactful. Addressing sociocultural biases is necessary to promote diversity and inclusion in STEM fields. Analyzing regional collaboration networks can identify best practices and foster knowledge sharing among ASEAN countries. Implementing context-specific reforms will ensure that solutions are tailored to the unique challenges and opportunities in Vietnam. Addressing these priorities will enable Vietnam to make informed decisions, strengthen STEM education, and develop a skilled workforce for sustainable economic growth.
Keywords: STEM education; curriculum integration; teacher training; sociocultural biases; public-private partnerships